The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/fishes7050228
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Fish Meal with a Bacteria Protein (Clostridium autoethanogenum Protein) Derived from Industrial-Scale Gas Fermentation: Effects on Growth and Gut Health of Juvenile Large Yellow Croakers (Larimichthys crocea)

Abstract: This study was conducted to investigate the effects of Clostridiumautoethanogenum protein (CAP) replacement for fish meal (FM) on growth performance, digestive enzyme activity, humoral immunity and liver and intestinal health in large yellow croakers (Larimichthys crocea). Four experimental diets were formulated by replacing FM with CAP at different levels—0% (CAP0), 15% (CAP15), 30% (CAP30) and 45% (CAP45). Triplicate groups of juveniles (initial weight = 11.86 ± 0.13 g) were fed the test diets to apparent sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…1, which was found already with remarkable abundance in our previous study [5]. Members of this genus are normally found as part of the autochthonous gut microbiota in several sh species, such as rainbow trout [43], yellow cat sh (Pelteobagrus fulvidraco) [44], European sea bass [45], yellowtail king sh [46], large yellow croaker (Larimichthys crocea) [47], pearly razor sh (Xyrichtys novacula) and gilthead seabream [5]. Here, Ralstonia was present in all samples, but its abundance was clearly enhanced in sh fed with shrimps.…”
Section: Discussionmentioning
confidence: 75%
“…1, which was found already with remarkable abundance in our previous study [5]. Members of this genus are normally found as part of the autochthonous gut microbiota in several sh species, such as rainbow trout [43], yellow cat sh (Pelteobagrus fulvidraco) [44], European sea bass [45], yellowtail king sh [46], large yellow croaker (Larimichthys crocea) [47], pearly razor sh (Xyrichtys novacula) and gilthead seabream [5]. Here, Ralstonia was present in all samples, but its abundance was clearly enhanced in sh fed with shrimps.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, it is crucial to find low-price and high-quality protein sources to replace FM. In this Special Issue, there is a published paper reporting a bacteria protein derived from industrial-scale gas fermentation [1]. Clostridium autoethanogenum protein (CAP) is a new type of microbial protein produced by the fermentation of Clostridium autoethanogenum with carbon monoxide from steel-making waste gas [2].…”
Section: Fish Nutrition and Physiologymentioning
confidence: 99%
“…Compared with traditional FM, CAP has a richer amino acid profile and contains a higher protein content, which gives it an inherent advantage as a protein ingredient. Zhang's study showed that dietary FM could be replaced by 15% CAP in feeds containing 40% FM without adversely affecting the growth of large yellow croakers and, to some extent, improving the immunity of the organism [1]. Besides, shrimp by-product (SBp) has been identified as a possible animal protein source by increasing shrimp production from captures and farms.…”
Section: Fish Nutrition and Physiologymentioning
confidence: 99%
“…Researches on L. crocea and M. salmoides showed that sh size is one of the key factors decided the optimal dietary level of CAP within the same sh species. For example, Zhang et al (2022) proved that CAP could replace 15% of shmeal for L. crocea with initial weight of 11.86g, higher dietary CAP (30% and 45%) reduced the growth and humoral immunity. But for the L. crocea with initial weight of 189.9 g, CAP can replace up to 30% of dietary shmeal protein without negative effects on the growth performance, intestinal healthy condition and esh quality (Wu et al 2022).…”
Section: Introductionmentioning
confidence: 99%